Локальные внутренние дифференцирования четырехмерных филиформных не лиевых алгебр Лейбница (SCIENCE and SOCIETY, 2022)
In this article, local inner derivations are studied of four-dimensional filiform of non-Lie Leibniz algebras. It is proved that every lo-